`-23/32 + 17/21 – 9/32 + 4/21`

`-23/32 + 17/21 – 9/32 + 4/21`

2 bình luận về “`-23/32 + 17/21 – 9/32 + 4/21`”

  1. -$\text{$\frac{23}{32}$ + $\frac{17}{21}$ – $\frac{9}{32}$ + $\frac{4}{21}$ }$
    $\text{=($\frac{-23}{32}$ – $\frac{9}{32}$) + ($\frac{17}{21}$ + $\frac{4}{21}$ ) }$
    \text{= -1 + 1}
    \text{= 0}

    Trả lời
  2. Giải đáp:
     
    Lời giải và giải thích chi tiết:
     Ta có: – 23/32 + 17/21 -9/32+ 4/21
          = -23/32 – 9/32 + 17/21+ 4/21
           = -32/32 + 21/21
            = -1 +1
            = 0

    Trả lời

Viết một bình luận

Câu hỏi mới